Evaluation of blackgram genotypes (Vigna mungo) under maize based intercropping systems - Manhas, Shilpa; SINGH, JANARDAN; rana, Khushboo; KAUR, NAVNEET (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur during rainy season of 2017, to evaluate the performance of blackgram genotypes under maize + blackgram intercropping system with different levels of nitrogen. The experiment was laid out in randomized block design comprising of 5 genotypes (Him mash-1, DKU-118, DKU-82, DKU-98 and DKU- 99) and two nitrogen levels (50 and 100% recommended dose of nitrogen). Experimental soil was silty clay loam in texture, acidic in reaction, low in available nitrogen, and medium in available phosphorus and potassium. Him mash-1 genotype showed significantly higher plant height, dry matter accumulation, relative growth rate, seeds per pod (6.7) and grain yield (240.5 kg/ha). The treatment, 100% recommended dose of nitrogen resulted in improved growth and higher primary branches per plant (9.9), pods per plant (22.6), seeds per pod (6.7), test weight (43.8 g) and grain yield (253.8 kg/ha). Him mash-1showed the best performance with 100% recommended dose of nitrogen applied to maize under maize + blackgram intercropping system in mid-hill region of Himachal Pradesh.